Policy and Regulatory Readiness of Industrial Carbon Capture and Storage (CCS) in Indonesia - Lenny Hidayat; Michael Timothy Tasliman; M. Ilham Ramadhan; Cholisa Amalia (Journal of Infrastructure Policy and Management, 2026)
Carbon Capture and Storage (CCS) is increasingly discussed as a policy option for decarbonizing hard-to-abate industries and supporting Environmental, Social, and Governance (ESG) implementation. In Indonesia, recent regulatory progress—especially Presidential Regulation No. 14 of 2024—has created an initial legal basis for CCS, but industrial deployment still depends on the coherence of policy, regulatory, and licensing arrangements across multiple sectors. This study examines the policy and regulatory readiness of industrial CCS in Indonesia through a qualitative, document-based analysis of laws, regulations, policy documents, peer-reviewed literature, and stakeholder consultations. The assessment is operationalized through eight readiness indicators: policy alignment, regulatory clarity, institutional coordination, licensing integration, environmental integrity, social safeguards, governance accountability, and Monitoring, Reporting, and Verification (MRV) readiness. The findings show that Indonesia has made important progress in establishing a legal foundation for CCS, yet readiness remains partial. The authority is fragmented across energy, environment, industry, licensing, transport, and sustainable-finance domains; long-term liability and post-closure stewardship remain insufficiently specified; and the integration of social safeguards and ESG-linked governance requirements is still limited. The article argues that industrial CCS can support the pillar of ESG, but only if Indonesia strengthens coordination, clarifies liability, streamlines licensing, and aligns CCS governance with ESG-oriented policy and reporting expectations.